2012
DOI: 10.1111/j.1365-313x.2012.04937.x
|View full text |Cite
|
Sign up to set email alerts
|

The RS domain of Arabidopsis splicing factor RRC1 is required for phytochrome B signal transduction

Abstract: SUMMARYPlants monitor the light environment through informational photoreceptors that include phytochromes. In seedling de-etiolation, phytochrome B (phyB), which is the most important member of the phytochrome family, interacts with transcription factors to regulate gene expression and transduce light signals. In this study, we identified rrc1 (reduced red-light responses in cry1cry2 background 1), an Arabidopsis mutant that is impaired in phyB-mediated light responses. A genetic analysis demonstrated that RR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
91
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 59 publications
(95 citation statements)
references
References 44 publications
3
91
1
Order By: Relevance
“…Phytochrome probably regulates the expression level (mRNA and protein level) or posttranslational modification of more upstream splicing regulators. RRC1, an SR-like splicing factor that is required for phyB signaling, is among these candidate upstream factors, because the R-responsive AS alterations of RS31 an SR34b have been shown to be partially dependent on RRC1 (21). Moreover, we found that some of the early R-responsive and phytochrome-dependent AS changes were substantially reduced in rrc1 mutants, whereas others were totally independent of RRC1 (Fig.…”
Section: Resultsmentioning
confidence: 49%
See 4 more Smart Citations
“…Phytochrome probably regulates the expression level (mRNA and protein level) or posttranslational modification of more upstream splicing regulators. RRC1, an SR-like splicing factor that is required for phyB signaling, is among these candidate upstream factors, because the R-responsive AS alterations of RS31 an SR34b have been shown to be partially dependent on RRC1 (21). Moreover, we found that some of the early R-responsive and phytochrome-dependent AS changes were substantially reduced in rrc1 mutants, whereas others were totally independent of RRC1 (Fig.…”
Section: Resultsmentioning
confidence: 49%
“…Time-course analysis revealed that the AS changes were detected within 1 h and peaked 3 h after pR irradiation (Fig. S2E), as was the case for cR irradiation (21). Next, we exposed etiolated seedlings to various intensities of 2-min pR or 3-h cR to confirm that the AS responses were dependent on the fluence rate of R (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations